Investigation Of Sea Wave Point Absorber, The Dual-Direction Mechanism - Zainol, Raja Ahmad Shurim Raja (Universiti Sains Malaysia, 2021)
Ocean wave energy is one type of renewable energy resources that can be consider more reliable compared to solar and wind energy due to it vast and tremendous amount of energy density. Due to several issue and challenge, the technology to develop a commercialise system that can harvest the ocean wave energy is still lack in several component or principle. Point absorber is one of the Wave Energy Converter (WEC) technology or principle which still under development and research that can be consider having a bright future. In this paper, the development of sea wave point absorber that can generate the electricity from both type of wave, crest and trough. The design is using the barrel cam mechanism that can use the dual direction motion and transfer it into one single rotation. The research started by designing the design using the CAD software which is SolidWorks. The boundaries and calculation of the natural frequency of the floater is defined and calculated before the simulation started. The design is undergoing the simulation of motion in SolidWorks while the simulation of energy density is conducted using the ANSYS software. The highest rotation per minute achieves on barrel cam 1 with floater C with 220.82 RPM while barrel cam 1 with floater B has the highest average rotation per minutes with 108.36 RPM. The floater C has the highest energy density with 21.25 J/Kg.